Analysis and Discussion of BOSS Construction Processes of Telecom Operators - Xiaojun Xie; Junjun Hu (Dianxin kexue)
BOSS construction processes of telecom operators and the development processes inside software vendors were analyzed based on the product line engineering framework.It was discussed that how to introduce the domain engineering to optimize and adapt existing processes to strengthen architecture management capability of the telecom operators,helping companies achieve IT strategic goals.